2021
DOI: 10.1021/acscatal.1c01347
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Platinum by Titania under an Oxidative Atmosphere: Contrary to Classical Strong Metal–Support Interactions

Abstract: Classical strong metal−support interaction (SMSI) has attracted intensive attention in the heterogeneous catalysis field; however, its crystalline TiO x overlayer and reversible feature often curtail the effect of classical SMSI on enhancing the catalytic performance of supported metal catalysts in oxidation reactions, especially at elevated temperatures. Here, we report the evidence that Pt nanoparticles can be encapsulated by an amorphous and permeable TiO x cover layer in Pt/TiO 2 catalysts under an oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…The phenomenon indicates that ceria could migrate onto the surface of Mo species due to strong metal-support interaction, in consistent with the observations of other metal catalysts supported on reducible oxides (e.g., CeO 2 , Nb 2 O 5 , TiO 2 , etc.). [42][43][44][45] On the other hand, the STEM-HAADF image shows that the porous structure of the Mo 2 C/ CeO 2 catalyst consists of lots of particles 15-75 nm in size (Figure S4), and together with the EDS mapping image, it is considered that the Mo 2 C is partially encapsulated by CeO 2 (Figure 1). The presence of CeO 2 species on the surface of Mo 2 C can be further supported by the HRTEM image of Mo 2 C/CeO 2 (Figure S4).…”
Section: Effect Of Mo Carburization On Ammonia Synthesis Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon indicates that ceria could migrate onto the surface of Mo species due to strong metal-support interaction, in consistent with the observations of other metal catalysts supported on reducible oxides (e.g., CeO 2 , Nb 2 O 5 , TiO 2 , etc.). [42][43][44][45] On the other hand, the STEM-HAADF image shows that the porous structure of the Mo 2 C/ CeO 2 catalyst consists of lots of particles 15-75 nm in size (Figure S4), and together with the EDS mapping image, it is considered that the Mo 2 C is partially encapsulated by CeO 2 (Figure 1). The presence of CeO 2 species on the surface of Mo 2 C can be further supported by the HRTEM image of Mo 2 C/CeO 2 (Figure S4).…”
Section: Effect Of Mo Carburization On Ammonia Synthesis Performancementioning
confidence: 99%
“…Moreover, it is well known that during hydrogen treatment of metal catalysts with reducible oxides (e.g., CeO 2 , Nb 2 O 5 , TiO 2 , etc.) as supports at high temperature, the reducible oxides could migrate onto the metal surface as a result of strong metal-support interactions [42][43][44][45]. During the carbonization process of Mo/CeO 2 in the presence of CH 4 and H 2 , there is the formation CeO 2 overlayers and particles on the surface of the Mo species for the sample with an appropriate Mo/CeO 2 ratio.…”
mentioning
confidence: 99%
“…Similar encapsulation effects have also been reported for Co (12), Ni (13,14), Au (15), and Cu (16) NPs. More recently, it was shown that hightemperature oxidative treatment can also lead to NP encapsulation (15,(17)(18)(19)(20). Potential benefits of SMSI encapsulation include enhanced resistivity against both NP coalescence and Ostwald ripening (21)(22)(23).…”
mentioning
confidence: 99%
“…Some important studies have demonstrated that strong metal-support interaction (SMSI) contributes to improved catalyst stability, catalytic activity, and control reaction selectivity. [16][17][18] Based on highly crystalline and nanoporous hexagonal boron nitride 2D materials, the construction of nonoxide-derived SMSI nanocatalyst exhibits high catalytic efficiency and durability in CO oxidation under simulated to realistic exhaust systems. 19 The Ru-MoO 3 catalyst with SMSI can achieve the selective CO 2 hydrogenation to CO with excellent activity and catalytic stability.…”
Section: Introductionmentioning
confidence: 99%